2016
DOI: 10.1007/s10067-016-3516-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of human leukocyte A, B, and DR antigens in Colombian patients with diagnosis of spondyloarthritis

Abstract: There is substantial evidence that non-B27 major histocompatibility complex (MHC) genes are associated with spondyloarthritis (SpA). Studies in Mexican and Tunisian populations demonstrated the association of SpA and human leukocyte antigen (HLA) B15. The purpose of this study was to evaluate the association of HLA-A, B, and DR antigens in a group of Colombian patients with a diagnosis of SpA. A total of 189 patients and 100 healthy subjects were included in the present study. All subjects underwent a complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 21 publications
3
14
1
Order By: Relevance
“…We could not confirm some other associations described in smaller AS or SpA cohorts elsewhere32–34 perhaps due to clinical heterogeneity. One small recent study of HLA-A, HLA-B, HLA-C and DRB1 alleles in 75 Moroccan patients with AS reported an allele frequency of HLA-B*27 of 32%, with associations also seen with B*57 , C*02 and DRB1*15 and negative associations with HLA-B*35 and B*49 32.…”
Section: Discussioncontrasting
confidence: 56%
“…We could not confirm some other associations described in smaller AS or SpA cohorts elsewhere32–34 perhaps due to clinical heterogeneity. One small recent study of HLA-A, HLA-B, HLA-C and DRB1 alleles in 75 Moroccan patients with AS reported an allele frequency of HLA-B*27 of 32%, with associations also seen with B*57 , C*02 and DRB1*15 and negative associations with HLA-B*35 and B*49 32.…”
Section: Discussioncontrasting
confidence: 56%
“…In addition to the expected increase in the frequency of HLA-B27, we also found an increased frequency of HLA-B15 in our patients with SpA. 14 Also, we reported a clear association between HLA-B27 with axial SpA including AS, and HLA-B15 with peripheral SpA including undifferentiated spondyloarthritis. 15 The objective of the present study was to establish the association of polymorphisms of ERAP1 and ERAP2 genes in Colombian patients with SpA with HLA-B27+ or HLA-B15+, and to evaluate how this association could be related to the clinical presentation of the disease, specifically with axial or peripheral predominance.…”
Section: How Might This Impact On Clinical Practice?supporting
confidence: 82%
“…In addition to the expected increase in the frequency of HLA-B27, we also found an increased frequency of HLA-B15 in our patients with SpA. 14 Also, we reported a clear association between HLA-B27 with axial SpA including AS, and HLA-B15 with peripheral SpA including undifferentiated spondyloarthritis. 15 …”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations